PENGARUH PRODUK DOMESTIK REGIONAL BRUTO ( PDRB ), TINGKAT INFLASI DAN JUMLAH PELANGGAN LISTRIK TERHADAP PENDAPATAN ASLI DAERAH (PAD) STUDI KASUS PADA 35 KABUPATEN / KOTA DI PROVINSI JAWA TENGAH (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study was to identify the variables that affect Local Revenue of the Government of Central Java Province . After reviewed the literature necessary that related to thhae variables defined in this study, this research Gross Regional Domestic Product , Inflation Rate and Total Customer Electricity could have impact Original Local Revenue. This research was a case study 35 regencies / municipalities in Central Java Province . Data analysis used panel data regression .Based on Normality Test showed that residual was to obtain a better panel data regression model this research used the Chow test and Hausman test . Chow Test results concluded that the FEM models was better than PLS models . While the results of Hauman test concluded that the FEM models was better than REM models . This means that the selected model is the model of FEM . Based on the FEM model the multiple linear regression equation is PAD = - 7.8289 + 2.3631.GRDP - 0.0021.INF + 0.0476.JPL . The result of model testing using adjusted R square and ANOVA technique was concluded that model was good.Then the result of hyphotheses testing procedure showed that The Inflation Rate and The Total of Electric Customers had no significant effect Original Local Revenue in Central Java Province. Only Gross Regional Domestic Product ( PDRB ) has a positive and significant impact Original Local Revenue. Keywords : Gross Regional Domestic Product , Inflation Rate , Total Electric Customers and Original Local Revenue .